2017
DOI: 10.1021/acs.cgd.7b00117
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I) 3,5-Diethyl-1,2,4-Triazolate (MAF-2): From Crystal Engineering to Multifunctional Materials

Abstract: Among various types of nonporous and porous coordination polymers, and as a subset of metal azolate frameworks (MAFs), Cu(I) 1,2,4triazolates are unique for their simple three-connected network topologies which can be controlled by their significant steric hindrance effects between the noncoordinative side groups. This perspective article discusses the crystal engineering, structures, and diversified properties of Cu(I) 1,2,4-triazolates, particularly focusing on the porous coordination polymer [Cu(detz)] (MAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Azoles and their derivatives are widely used as organic connectors in supramolecular coordination chemistry, leading to a variety of networks due to their numerous coordination modes. This includes monodentate, bidentate chelating, or bidentate bridging modes, depending on the position and the nature of the substituent at the azole ring. The types of architecture range from 1D azole coordination polymers (ACPs) to 2D or 3D metal-azolate networks (MANs) and frameworks (MAFs). It is quite challenging to control the construction of polynuclear complexes, as structural modifications of building blocks influence the final structural motifs through covalent bonding and various weak interactions. Therefore, the selection of organic connectors with proper length, flexibility, and symmetry is critical to obtain special topology structures.…”
Section: Introductionmentioning
confidence: 99%
“…Azoles and their derivatives are widely used as organic connectors in supramolecular coordination chemistry, leading to a variety of networks due to their numerous coordination modes. This includes monodentate, bidentate chelating, or bidentate bridging modes, depending on the position and the nature of the substituent at the azole ring. The types of architecture range from 1D azole coordination polymers (ACPs) to 2D or 3D metal-azolate networks (MANs) and frameworks (MAFs). It is quite challenging to control the construction of polynuclear complexes, as structural modifications of building blocks influence the final structural motifs through covalent bonding and various weak interactions. Therefore, the selection of organic connectors with proper length, flexibility, and symmetry is critical to obtain special topology structures.…”
Section: Introductionmentioning
confidence: 99%
“…The design of coordination polymers with a predictable secondary building unit (SBU) and dimensionality is a quasi-impossible task, but the quest remains of great interest for the discovery of new materials with desired properties such as gas adsorption, sensing, thermo-chromism, magnetism, conductivity, redox-activity, , catalysis, , nonlinear optical behavior, , and luminescence. , Recent reviews on CPs formed by mono- and dithioethers with CuX salts (X = Cl, Br, I) revealed that, when X = I, the SBU had a strong tendency to form closed cubanes (Cu 4 I 4 ) and 1D staircase polymeric structures, whereas the rhomboid Cu 2 X 2 S 4 SBU is predominately noted when X = Cl or Br. The key property is that the cubanes show luminescence regardless of the ligand, whereas the rhomboids and staircase motifs are almost always weakly or not emissive. ,, Also, the presence of 2D and 3D CPs increases drastically when semirigid or rigid dithioethers are used as assembling ligands. ,, The interest in 2D and 3D CPs stems from the possibility to form MOF-like materials .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of CityU-7 as a water-stable MOF also offers fundamental insight into materials design. In general, better water stability can be achieved by enlisting hard–hard (e.g., as in Cr 3+ , Zr 4+ -carboxylate) bonding or using softer coordination bonds based on, for example, nitrogen donors and metal ions including Cu­(I) and other transition metals. That is to say, most Cu­(I)-based MOF solids are constructed through N-donor linkers such as pyrazolate and pyridine, while Cu­(I)-carboxylate links are rarely featured in MOF structures. , This observation is partly due to the soft nature of Cu­(I) that tends to refrain from the hard carboxyl group and partly due to Cu­(I) being prone to oxidization and disproportionation.…”
mentioning
confidence: 99%